HLA Matching Trumps Donor Age: Donor-Recipient Pairing Characteristics That Impact Long-Term Success in Living Donor Kidney Transplantation in the Era of Paired Kidney Exchange. Issue 7 (July 2016) - Milner, John; Melcher, Marc L.; Lee, Brian; Veale, Jeff; Ronin, Matthew; D'Alessandro, Tom; Hil, Garet; Fry, Phillip C.; Shannon, Patrick W.
Abstract : Background: We sought to identify donor characteristics influencing long-term graft survival, expressed by a novel measure, kidney life years (KLYs), in living donor kidney transplantation (LDKT). Methods: Cox and multiple regression analyses were applied to data from the Scientific Registry for Transplant Research from 1987 to 2015. Dependent variable was KLYs. Results: Living donor kidney transplantation (129 273) were performed from 1987 to 2013 in the United States. To allow sufficient time to assess long-term results, outcomes of LDKTs between 1987 and 2001 were analyzed. After excluding cases where a patient died with a functioning graft (8301) or those missing HLA data (9), 40 371 cases were analyzed. Of 18 independent variables, the focus became the 4 variables that were the most statistically and clinically significant in that they are potentially modifiable in donor selection ( P <0.0001; ie, HLA match points, donor sex, donor biological sibling and donor age). HLA match points had the strongest relationship with KLYs, was associated with the greatest tendency toward graft longevity on Cox regression, and had the largest increase in KLYs (2.0 year increase per 50 antigen Match Points) based on multiple regression. Conclusions: In cases when a patient has multiple potential donors, such as through paired exchange, graft life might be extended when a donor with favorable matching characteristics is selected.